Evaluation of the relationship of disease activity with neutrophile to lymphocyte ratio and platelet to lymphocyte ratio in patients with peptic ulcer and gastritis - Gulbagci, Burcu; Sametoglu, Fettah; Cengiz, Hasret; Varim, Ceyhun (International Journal of Research in Medical Sciences, 2020)
Background: Dyspepsia is a confusing complaint in terms of patient approach and management. Since the most important clinical diagnoses that occur with dyspeptic complaints are gastroduodenitis, peptic ulcer disease and gastric-esophageal cancers, endoscopic evaluation method is often preferred in the diagnosis. It has been shown that NLR (neutrophil to lymphocyte ratio) can be an important marker in many chronic systemic diseases, especially malignancies. Since upper gastrointestinal endoscopy is an invasive and costly procedure, NLR and PLR (Platelet to lymphocyte ratio) may be useful as a new marker to help in the diagnosis of gastritis and peptic ulcer. In our study, we aimed to investigate how NLR and PLR changes seen in patients with gastritis and peptic ulcer diseases. Methods: A total of 906 patients who applied to the internal medicine clinic of our hospital between January 2016 and September 2017 were included in the study. The demographic data, drugs, endoscopy and biopsy results and hemogram parameters of the patients were obtained from the outpatient clinic records. NLR and PLR values were calculated and statistically interpreted. Results: According to the endoscopy results, a total of 906 patients with 311 (34.3%) gastritis, 288 (31.8%) peptic ulcer and 307 (33.9%) normal findings were included in to the study. Male to female ratios were 55% to 45% in gastritis patients, 55,6% to 44,4% in peptic ulcer patients and 53,4% to 46,6% in normal subjects. The median age of the patients was 50 years (18-82 years). The median NLR and PLR ratios were 1.82 (0.54-8.35) and 107.8 (46.27-446.43) in the gastritis group, 1.9 (0.61-9.86) in the peptic ulcer group and 110.95 (44.03-340.65) and 1.71 (0.56-12.89) and 106.02 (40.41-397.62) in the normal group. While a significant difference was obtained between the groups in terms of NLR ((p=0.048), no significant difference was found for PLR (p=0.422). Conclusions: In our study, a statistical significant difference was found between patients with gastritis and peptic ulcer and normal subjects in terms of NLR, but this difference was not at a level that could be used in clinical practice.